Factores asociados al consumo de sustancias de los trabajadores divorciados del Ecuador - Chávez Romero, Verónica Elizabeth (2018)
Abstract:The divorced people, being a vulnerable population, face this state in different ways, being one of them the consumption of substances. This research is called factors associated with the consumption of substances in workers divorced from Ecuador, the sample was formed by 169 workers from university communities. An online battery was applied with 4 standardized instruments to measure alcohol consumption, tobacco, other drugs, psychological inflexibility and stress, as well as an ad hoc survey of sociodemographic data. For the interpretation of results, descriptive analysis was used, where it was found that 54.4% of men and 59.4% of women have a prudent consumption of alcohol. Through Chi-Square tests it was found that sex, type of occupation and type of housing were associated with alcohol consumption. On the other hand, Pearson's correlation found that stress and psychological inflexibility were significantly associated with alcohol consumption; and through t-student tests, it was found that women and administrative staff are more stressed.